A Mini Review of the Zoonotic Threat Potential of Influenza Viruses, Coronaviruses, Adenoviruses, and Enteroviruses - Bailey, Emily S.; Fieldhouse, Jane K.; Choi, Jessica Y.; Gray, Gregory C. (Frontiers in Public Health, 2018)
During the last two decades, scientists have grown increasingly aware that viruses are emerging from the human-animal interface. In particular, respiratory infections are problematic; in early 2003 WHO issued a worldwide alert for a previously unrecognized illness that was subsequently found to be caused by a novel coronavirus [Severe Acute Respiratory Syndrome (SARS) virus]. In addition to SARS, other respiratory pathogens have also emerged recently, contributing to the high burden of respiratory tract infection-related morbidity and mortality. A number of emerging viruses have been influenza viruses, coronaviruses, enteroviruses, and adenoviruses. As the genesis of these emerging viruses is not well understood and their detection normally occurs after they have crossed over and adapted to man, ideally, strategies for such novel virus detection should include intensive surveillance at the human-animal interface, particularly if one believes the paradigm that many novel emerging zoonotic viruses first circulate in animal populations and occasionally infect man before they fully adapt to man; early detection at the human-animal interface will provide earlier warning. Here we review recent emerging virus treats for these four groups of viruses.